Heat-killed Salmonella Typhimurium protects mice against carbon ion radiation. Issue 10 (October 2020) - Liao, Zebin; Liu, Zhe; Gong, Zhenyu; Hu, Xuguang; Chen, Yuanyuan; Cao, Kun; Zhang, Hong; Gan, Lu; Chen, Juxiang; Yang, Yanyong; Cai, Jianming
Objective: Patients receiving carbon-ion radiation therapy and astronauts exploring outer space are inevitably exposed to heavy ion radiation. The aim of this study was to develop radioprotectors to minimize the injuries induced by carbon ion radiation. Methods: Heat-killed Salmonella Typhimurium (HKST) was administered to mice by gavage prior to irradiation with a 12 C 6+ heavy ion accelerator. Hematoxylin and eosin staining and immunofluorescence TdT-mediated dUTP Nick-End Labeling staining were used to assess the radioprotective effect of HKST on organ damage and levels of apoptosis, respectively, in mice. To investigate the mechanism underlying the radioprotective effect of HKST, levels of the pro-apoptotic proteins BAX and caspase 3 as well as interferon-regulatory factor (IRF) 3/7 in the femur, testis and intestine were assessed using immunofluorescence. Results: Injuries induced by carbon ion radiation were significantly eased by pretreatment with HKST. Both apoptosis and high expression levels of pro-apoptotic proteins induced by heavy ion radiation were inhibited by HKST pretreatment. The radioprotective effect of HKST was associated with stimulation of Toll-like receptor signaling mediated by enhanced IRF3 and IRF7 signaling. Conclusion: HKST was an effective radioprotector alleviating damage to multiple organs caused by heavy ion radiation.